Fabrication-structure-properties relations of nano-sized NiO incorporated PZT ceramics - S. Jiansirisomboon (2018)
Ferroelectric PZT/NiO ceramics were fabricated using a solid-state mixed-oxide method. Effects of sintering temperature and content of nano-sized NiO addition (i.e. 0, 0.1, 0.5 and 1 wt%) on structure and densification of the ceramics were investigated. The tetragonality in tetragonal unit cell of pure PZT was found to decrease with increasing NiO content for sintering temperatures in between 1100 and 1200 °C. At a higher temperature of 1250 °C, high degree of tetragonality was maintained regardless of added NiO concentration. Density tended to increase with increasing amount of NiO. The grain size of PZT ceramics was also significantly reduced even with only 0.1 wt% NiO addition. The densest samples sintered at 1250 °C were chosen for mechanical and electrical measurements. Addition of NiO was found to improve hardness and only slightly affect fracture toughness. The maximum room temperature dielectric constant was achieved in PZT/0.1 wt% NiO sample which seemed to be the optimized composition in this study. © 2009 Elsevier B.V. All rights reserved.